Significance of Information Technology in Hotel Management - Pradhan, Bibhuti Bhusan (International Journal of Psychosocial Rehabilitation, 2019)
Since country's tourism and economic development is increasing rapidly, the competition in the hotel industry market is increasing rapidly. People can only get healthy and adequate development by developing the methods and means of their management and constantly improving their level of service. Hence, the computer management of hotel operation has become the most essential task in hotel industries. The enhancement in computer technology leads to create potential opportunity to bring the change in hotel management practices. This papers provide a brief introduction to the architecture of the hotel management framework in conjunction with software engineering means for the study of viability, design and specifications. The complete system is separately divided into modules and introduces the function, while providing the database management a logical structure and a set of criteria and the. These guidelines and analyses basically fulfil the requirements of design of the information technology-based hotel management system, in order to improve the hotel management's service efficiency and quality.